ChemInform Abstract: Copper‐Catalyzed Consecutive Reaction to Construct Quinazolin‐4(3H)‐ones and Pyrido[2, 3‐d]pyrimidin‐4(3H)‐ones. Issue 24 (27th May 2016) - Li, Ting; Chen, Minglu; Yang, Lei; Xiong, Zhengxin; Wang, Yongwei; Li, Fei; Chen, Dongyin
Abstract: The title reaction starts from easily available 2‐halobenzamides [e.g. (I)] or 2‐halonicotinamides (X) and proceeds probably via aromatic nuleophilic substitution of azide/copper catalyzed reduction/imine formation/cyclization/oxidation sequence.